2017
DOI: 10.1080/14756366.2017.1335310
|View full text |Cite
|
Sign up to set email alerts
|

Natural extracellular nanovesicles and photodynamic molecules: is there a future for drug delivery?

Abstract: Photodynamic molecules represent an alternative approach for cancer therapy for their property (i) to be photo-reactive; (ii) to be not-toxic for target cells in absence of light; (iii) to accumulate specifically into tumour tissues; (iv) to be activable by a light beam only at the tumour site and (v) to exert cytotoxic activity against tumour cells. However, to date their clinical use is limited by the side effects elicited by systemic administration. Extracellular vesicles are endogenous nanosized-carriers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 132 publications
0
24
0
Order By: Relevance
“…Recent studies have shown that most of the circulating microRNAs detectable serum and saliva are concentrated in tumor-derived exosomes [152]. Extensive studies have shown that tumor-derived exosomes from either tumor cells or extracellular fluids of cancer patients can be used as biomarkers because they have a unique molecular signature on their biocontents (proteins, DNA/RNA molecules) [153][154][155]. A list of exosomes isolated from biofluids of cancer patients used as biomarkers were prepared with details in previous studies [33,40].…”
Section: Exosomes As Cancer Diagnostic Biomarkersmentioning
confidence: 99%
“…Recent studies have shown that most of the circulating microRNAs detectable serum and saliva are concentrated in tumor-derived exosomes [152]. Extensive studies have shown that tumor-derived exosomes from either tumor cells or extracellular fluids of cancer patients can be used as biomarkers because they have a unique molecular signature on their biocontents (proteins, DNA/RNA molecules) [153][154][155]. A list of exosomes isolated from biofluids of cancer patients used as biomarkers were prepared with details in previous studies [33,40].…”
Section: Exosomes As Cancer Diagnostic Biomarkersmentioning
confidence: 99%
“…Exosomes are extracellular nanovesicles of 40-180 nm secreted by all cells and capable of modulating physiological or pathological processes, including tumour progression, through transmitting into target cells their cargo (lipids, proteins, DNA, mRNA or microRNA) [18][19][20][21][22][23][24] . Exosomes are involved in a broad panel of cellular phenomena, including intercellular communication, elimination of toxic substances and drug delivery 14,18,25,26 . The acid release of the exosomes is key in tumour growth, tumour progression and metastasis 18,24,27 .…”
Section: Introductionmentioning
confidence: 99%
“…f) pH, tumor growth and invadopodia [61,63]. g) pH, cancer growth and the metastatic process [63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%